Effect of Zinc Oxide, Silica and Kaolin on the Compressive Strength of Portland Cement Mortar - Mohammed, S.A.S. (Newswood Limited, 2021)
This study aims to investigate the effect of adding Zinc oxide, Silica and Kaolin on the compressive strength of Portland cement mortar. The mix portion of mortar was prepared with a water to cement ratio of 1:2, cement to sand ratio of 1:2.5 and different percent of additives (0.2, 5 and 10). Results show that cement mortar, which did not contain Zinc Oxide (ZnO), increases the compressive strength (CS)of blended mortar. After 2 days, the best result was obtained for an additive of 5 Kaolin and 5 Silica with a 33.48 increase in compressive strength relative to the control. However, after 28 days the best result attained was for an additive of 5 micro silica with a 13.26 increase in compressive strength relative to control. Addition of ZnO, in different particle sizes, resulted in negative effect on compressive strength contrary to some publications which indicate that the methods and blending ratio has significant effect in the CS. The molecular interaction, electron distribution and cohesion forces affect the CS. Â© 2021 Newswood Limited. All rights reserved.